An analogy between maxillary anterior teeth dimensions measured using facial proportions and Chu proportion gauge: an in vivo study: An analogy between maxillary anterior teeth dimensions - Kodipalli, Sravalli; Praveen, M; Kothuri, Ravalika N (International Journal of Dental Materials, 2022)
Background: A fine balancing of geometric concepts and artistic abilities is required while designing smiles. One of the key elements that make up the smile frame is tooth size. The maxillary front teeth are the most noticeable in the smile arch, therefore choosing the right tooth size and positioning it in the maxilla improves both aesthetics and treatment outcomes.Aim: This study aimed to compare the dimensions of maxillary anterior teeth measured with vernier callipers and CHU proportion gauge with facial proportions such as intercanthal distance, interalar width and bizygomatic width.Materials and Methods: On a sample of 100, Facial proportions, mesiodistal width, and height of maxillary anterior teeth were recorded using digital callipers and a Chu proportion gauge. The recorded data were subjected to statistical analysis. Mean comparisons of each width were done using a t-test, ANOVA and Tukey’s Post-hoc test considering a p-value less than 0.05 to be statistically significant.Results: Mean values of the combined width of anteriors calculated using Chu gauge was 45.08, and that calculated using Vernier Callipers was 45.85. Multiplying the factor 1.47 to Inner canthal width and 1.42 to Interalar width results in the combined width of the maxillary anterior teeth. A mean difference of 0.02620 ± 0.91777 and 0.4988 ± 0.91777 exists between Inner canthal and Combined Chu’s width with a 0.04% and 0.34% error in younger and elder age populations, respectively. A mean difference of -11.4775 ± 0.91777 and -11.6039 ± 0.91777 exists between Combined mesiodistal width obtained by using Chu’s width and bizygomatic width with a 0.01% error in younger and elder age populations, respectively.Conclusions: This study reported a negligible 0.7 difference in the means of the combined width of anteriors calculated using Chu gauge and Vernier Callipers. Hence, these two methods can be used as alternatives to calculate the width of anterior teeth.